Development of an integrated learning device Wordwall application: An elementary school student's science literacy skills - Sugiharti, Asih; Buchori, Achmad; Sulianto, Joko (Indonesian Journal of Educational Development (IJED), 2025)
The low skills of science teachers, who often lack adequate education levels, mastery of the subject matter, and effective teaching techniques, negatively impact literacy. Therefore, this study aims to develop an integrated learning tool for Wordwall applications to enhance students' scientific literacy skills, ensuring validity, practicality, and effectiveness. This study employed a research and development approach with a four-dimensional (4D) model design. We conducted this research at Public Elementary School 02 Wonokerso. The data collection instruments used were validity sheets, student worksheets, teacher and student response questionnaires, and assessment questions. The study's findings indicated that the learning tools met valid criteria, with the module assessment, student worksheet, and assessment question scores being 82.41, 84.09, and 84.17, respectively. Practicality tests from student and teacher questionnaires meet practical criteria (92.52 and 93.75), respectively. The learning tools are helpful because the "Paired Samples Correlations" (Sig. value of 0.00) and the results of the N-Gain Test fall into the moderate category (average 0.384 and 0.222). Therefore, it is concluded that the proposed integrated Wordwall learning device is valid, practical, and effective. Teachers can use Wordwall's interactive activities to improve primary school science literacy. Wordwall promotes active, fun learning in groups and individually, creating a dynamic learning environment.